Radiographic interpretation by nurse practitioners in a minor injuries unit. Issue 1 (January 1996) - Freij, R M; Duffy, T; Hackett, D; Cunningham, D; Fothergill, J
Abstract : OBJECTIVE: To compare nurse practitioners with senior house officers (SHOs) for their ability to request and interpret correctly a limited range of x ray views of patients attending a minor injuries unit. DESIGN: Retrospective analysis of case records. METHODS: 150 accident and emergency (A&E) records with x ray requests were randomly selected from the SHOs' first, second, and third 2-month period of their 6-month appointments; 150 record cards were randomly selected from a nearby minor injuries unit over the same period. Copies of the records were reviewed blind and a decision made as to whether x ray requests were appropriate; x ray interpretation was compared with that of a consultant radiologist. RESULTS: 106 x rays were taken on the MIU patients (71%) and 124 on the A&E patients (83%). There was no statistically significant differences in the ability of the nurse practitioners and the SHOs to request and interpret appropriate x rays. In both groups the decision to carry out an x ray was considered appropriate in 70% of patients; x rays were positive in about one third. The sensitivity of radiological interpretation was 93% in both groups, and there were 2% missed positives. CONCLUSIONS: Appropriately trained nursae practitioners are at least as good as SHOs in recognising the need for an x ray and are as competent in their interpretation.